Computed Tomography Scan for Diagnosis of Osteoarthritis: Rare Localization in the Shoulder in a Twelve-Year-Old Boy - Dragana Nikolić; Đurđica Milković; Vladimir Jurišić (Acta Clinica Croatica, 2020)
Acute osteomyelitis is pyogenic infection of the bone and bone marrow. We report a case of successful diagnosis and treatment in a 12-year-old boy with right shoulder joint osteoarthritis. On admission, he was febrile (39.0 ºC) with pain in his right shoulder. Laboratory and biochemistry findings were as follows: leukocytes 10.9x109/L; hemoglobin 122 g/l; fibrinogen 34.7; C-reactive protein 56.8. No changes were observed using conventional radiography. Computed tomography (CT) scan was conducted on the right limb using LightSpeed 16 slices in native and contrast series. The area of interest was shown on axial section, less dense fluid within the joint cavity with a thickened capsule and joint soft tissue swelling around the joint. On bone structures, CT morphological changes were not observed. After deterioration of the condition despite antibiotic therapy, surgery had to be performed. The purulent content was removed by surgery. Prolonged antibiotic therapy and rehabilitation led to improvement of the condition. At two-month follow-up, ultrasonography and CT scan showed that there were no pathologic changes, while magnetic resonance imaging showed minimal tissue fibrosis that did no require surgical treatment.